Kontekstualisasi Ekonomi Syariah dalam Distribusi Pendapatan dan Kekayaan: Perspektif Q.S Al-Hasyr Ayat 7 - Prasetyo, Iin; Syahriza, Rahmi; Tarigan, Azhari Akmal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
Sharia economics is essentially a system that builds justice, balance, and sustainability in achieving individual and community welfare. One of these economic systems is built with a wealth and income distribution policy. Improper distribution results in most of the wealth and income only being enjoyed by capitalists and triggers social inequality so that an income redistribution policy is needed to overcome this inequality. Surah Al-Hasyr verse 7 explains that wealth must be distributed as an effort of justice in achieving prosperity. Surah Al-Hasyr verse 7 in the contextualization of sharia economics in Indonesia explains that zakat is an important instrument of state revenue whose distribution is centrally managed by Baznas. Keywords: sharia economics, distribution, redistribution, zakat